Factors associated with non-adherence and misuse of opioid maintenance treatment medications and intoxicating drugs among Finnish maintenance treatment patients. (1st May 2016) - Launonen, Essiina; Wallace, Isla; Kotovirta, Elina; Alho, Hannu; Simojoki, Kaarlo
Highlights: We examine the predictors for non-adherence and misuse among Finnish opioid maintenance treatment (OMT) patients. Non-adherence is associated with BNX medication and its low (<9.0 mg) daily dose. IV use of illicit OMT medications is associated with BNX medication with low dose. IV use of other intoxicating drugs is more common among those who use illicit drugs. More effort should be made to reduce concurrent injecting use during OMT. Abstract: Background: The intravenous (IV) use of opioid maintenance treatment (OMT) medications and other intoxicating drugs among OMT patients is a challenge for many OMT units and affects treatment outcomes. The aim of this study is to examine factors associated with IV use of OMT medications and other intoxicating drugs among Finnish OMT patients. Methods: A cross-sectional study was conducted among all Finnish OMT patients of whom 60% (n = 1508) participated. The data were collected by anonymous questionnaire. Binominal regression analysis with unadjusted and adjusted ORs was conducted to evaluate predictors for IV use. Findings: Factors associated with the injection of a patient's own OMT medication were: being treated with buprenorphine-naloxone (BNX) (OR 2.60, p = 0.005) with a low dose (<9.0 mg/day; OR 5.70, p < 0.001) and being treated in a health-care centre (OR 2.03, p = 0.029). Factors associated with the injection of illicit OMT medications were: being treated with BNX (OR 5.25, p < 0.001) with a low dose (<9.0 mg/day; OR 2.89, p = 0.017), lack of psychosocial support (OR 2.62, p < 0.001) and concurrent use of psychotropic medications from illicit sources (OR 4.28, p < 0.001). Associated factors for the injection of other intoxicating drugs were: concurrent use of illicit drugs (OR 1.72, p = 0.015), psychotropic medications from illicit sources (OR 4.78, p < 0.001) and from a doctor (OR 1.93, p = 0.004). Conclusions: More effort should be made to reduce concurrent injecting use during OMT. This may be done by addressing concurrent substance use orders more effectively, by ensuring that patients receive an optimal BNX dose and by providing more psychosocial support.